Selecting Electronic Publications: The Development of a Genre Statement. - Lila A. Faulkner; Karla L. Hahn (Issues in Science and Technology Librarianship, 2001)
While electronic publications offer opportunities to enhance collections and services, they unfortunately raise significant issues with regard to the duplication of investment, conversion from ownership to licensing of primary source materials, and concerns with long-term access to information. Acquiring these resources demands substantial amounts of staff time in selection, acquisition, cataloging, and management. This article describes the development and creation of a genre statement for a subset of electronic resources that the University of Maryland Libraries have termed "electronic publications." Issues covered include the factors that created a need for the genre statement, the process followed to develop it and the issues contained in the genre statement. The development of a genre statement provided us with an opportunity to assess emerging problems and a chance to codify and disseminate developing best practices. Its completion marks the first step in a process to create a coherent program for the evaluation and selection of electronic publications.